Production of Bioagent for Calcium-Based Biocement - Stabnikov, Viktor (International Journal of Biotechnology for Wellness Industries, 2016)
Biocements and biogrouts are developing extensively as new materials alternative to cement and toxic chemical grouts. The most popular type of biocement is a mixture of urease-producing bacteria, urea and calcium salt. Thus, development of biotechnology to produce biomass of urease-active bacteria for large-scale biocementation is an important biotechnological task. Two strains of urease-producing bacteria, Yaniella sp. VS8 and Bacillus sp. VS1 that synthesized inducible and constitutive urease, respectively, were used in the present study. It was shown that low cost biomass of urease-active bacteria can be produced from the hydrolyzed excessive activated sludge of municipal wastewater treatment plant. The biomass of Yaniella sp. VS8 grown in this medium diminished the hydraulic conductivity of sand from 4.8×10-4 m/s to 5∙10-8 m/s after several biotreatments with solution of 1.5 M urea and 0.75M СаCl2.